Insight Into Polysaccharides From Panax ginseng C. A. Meyer in Improving Intestinal Inflammation: Modulating Intestinal Microbiota and Autophagy - Wang, Dandan; Shao, Shuai; Zhang, Yanqiu; Zhao, Daqing; Wang, Mingxing (Frontiers in Immunology, 2021)
Polysaccharides from Panax ginseng C. A. Meyer (P. ginseng) are the main active component and exhibit significant intestinal anti-inflammatory activity. However, the unclear therapeutic mechanism of ginseng polysaccharide hinders the application for medicine or functional food. In this study, a polysaccharide was isolated from P. ginseng (GP). The primary structure and morphology of GP were studied by HPLC, FT-IR spectra, and scanning electron microscopy (SEM). Further, its intestinal anti-inflammatory activity and its mechanism of function were evaluated in experimental systems using DSS-induced rats, fecal microbiota transplantation (FMT), and LPS-stimulated HT-29 cells. Results showed that GP restored mTOR-dependent autophagic dysfunction via modulating the structure of gut microbiota and blocking the TLR4-MyD88 pathway. Consequently, active autophagy suppressed inflammation through the inhibition of NF-κB, oxidative stress, and the release of cytokines. Therefore, our research provided a rationale for future investigations into the relationship between microbiota and autophagy via TLR4 and revealed the therapeutic potential of GP for inflammatory bowel disease.